Active MEMS metamaterials for THz bandwidth control - Shih, Kailing (2017)
We experimentally demonstrate a microelectromechanical system (MEMS) based metamaterial with actively tunable resonance bandwidth characteristics, operating in the terahertz (THz) spectral region. The broadband resonance characteristic feature of the MEMS metamaterial is achieved by integrating sixteen microcantilever resonators of identical lengths but with continuously varying release lengths, to form a supercell. The MEMS metamaterial showed broadband resonance characteristics with a full width half maximum (FWHM) value of 175 GHz for resonators with a metal thickness of 900 nm and was further improved to 225 GHz by reducing the metal thickness to 500 nm. The FWHM resonance bandwidth of the MEMS metamaterial was actively switched to 90 GHz by electrostatically controlling the out-of-plane release height of the constituent microcantilever resonators. Furthermore, the electrically controlled resonance bandwidth allows for the active phase engineering with relatively constant intensity at a given frequency based on the reconfiguration state of the MEMS metamaterial. This enables a pathway for the realization of actively controlled transmission or reflection based on dynamically programmable THz metamaterials.